2014
DOI: 10.4049/jimmunol.1400176
|View full text |Cite
|
Sign up to set email alerts
|

IL-33–Induced Hematopoietic Stem and Progenitor Cell Mobilization Depends upon CCR2

Abstract: IL-33 has been implicated in the pathogenesis of asthma, atopic allergy, anaphylaxis, and other inflammatory diseases by promoting the production of proinflammatory cytokines and chemokines or Th2 immune responses. In this study, we analyzed the in vivo effect of IL-33 administration. IL-33 markedly promoted myelopoiesis in the bone marrow and myeloid cell emigration. Concomitantly, IL-33 induced hematopoietic stem and progenitor cell (HSPC) mobilization and extramedullary hematopoiesis. HSPC mobilization was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 38 publications
5
37
0
1
Order By: Relevance
“…In a previous study, we found that IL-33 can increase neutrophil phagocytic activity in a peritoneal C. albicans infection (13,14). In the current study, an in vivo phagocytosis assay demonstrated that IL-33-primed CD11b + Ly6G hi neutrophils had a higher capacity to phagocytose FITC-labeled C. albicans in kidneys at 1 d postinfection (Fig.…”
Section: Il-33 Promoted the Phagocytic Activity Of Neutrophilsmentioning
confidence: 60%
See 2 more Smart Citations
“…In a previous study, we found that IL-33 can increase neutrophil phagocytic activity in a peritoneal C. albicans infection (13,14). In the current study, an in vivo phagocytosis assay demonstrated that IL-33-primed CD11b + Ly6G hi neutrophils had a higher capacity to phagocytose FITC-labeled C. albicans in kidneys at 1 d postinfection (Fig.…”
Section: Il-33 Promoted the Phagocytic Activity Of Neutrophilsmentioning
confidence: 60%
“…However, infusion of large amounts of IL-33 could suppress immunopathology potently in two ways: by effective early fungal clearance and by inducing Th2 immunity, which has an anti-inflammatory effect. This dual action of IL-33 was a surprise, because in a previous study of a model of Candida sepsis we found that IL-33 potentiates neutrophil infiltration into peritoneum via the production of CXCR2 chemokines by macrophages (13,14). Thus, it appears that IL-33 has evolved functionally to provide a strategy whereby the kidney protects itself from damage by pathogens and immunopathology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…IL-33, in particular, has been considered to play a possible role in myeloproliferative neoplasm biogenesis. 46,47 The circulation level of IL-15 has also been reported to be increased in the patients with MF. 32 An MF SVEC cell line promoted the generation of greater numbers of hematopoietic progenitor cells from normal splenic CD34…”
Section: Org Frommentioning
confidence: 99%
“…Other than targeting various immune cells during inflammation, IL-33 also targets hematopoietic stem and progenitor cells to promote myelopoiesis and myeloid cell migration [20].…”
Section: Stem Cells Understand the Language Of Cytokinesmentioning
confidence: 99%